A dynamic auction for multi-object procurement under a hard budget constraint - Ludwig Ensthaler; Thomas Giebe (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
We present a new dynamic auction for procurement problems where payments are bounded by a hard budget constraint and money does not enter the procurer's objective function.
urn:nbn:de:bvb:19-epub-13244-4
Keywords: D21; D44; D45; D82; 330; Auctions; Mechanism Design; Knapsack Problem; Dominant Strategy; Budget; Procurement; Auktionstheorie; Mechanismus-Design-Theorie; Auktionstheorie; Beschaffung; Budgetrestriktion; Theorie